2008
DOI: 10.17221/1857-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metribuzin on rainbow trout (Oncorhynchus mykiss)

Abstract: AbstrAct:The aim of this study was to assess the effect of metribuzin on rainbow trout (Oncorhynchus mykiss). An experimental group of fish was exposed to Sencor 70 WG pesticide product (active substance 70% of metribuzin). The acute semistatical toxicity test lasting 96 h was performed on rainbow trout juveniles. The 96hLC50 value of Sencor 70 WG was 89.3 mg/l. An examination of the haematological and biochemical profile and histopathological tissue examinations were performed on one-to two-year-old rainbow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 21 publications
11
26
0
Order By: Relevance
“…In rodents, the dominant phase I metabolic reaction for triazine pesticides is cytochrome P450-mediated N-dealkylation (Hanioka et al, 1999 a,b). Triazine pesticides have a direct effect on kidney structure and function in freshwater fish (Velisek et al, 2008(Velisek et al, , 2009b. In our experiment, the caudal kidney of carp with chronic exposure to simazine showed destruction of the tubules, although chronic exposure to terbutryn had no effect on caudal kidney.…”
Section: Triazinesmentioning
confidence: 42%
See 2 more Smart Citations
“…In rodents, the dominant phase I metabolic reaction for triazine pesticides is cytochrome P450-mediated N-dealkylation (Hanioka et al, 1999 a,b). Triazine pesticides have a direct effect on kidney structure and function in freshwater fish (Velisek et al, 2008(Velisek et al, , 2009b. In our experiment, the caudal kidney of carp with chronic exposure to simazine showed destruction of the tubules, although chronic exposure to terbutryn had no effect on caudal kidney.…”
Section: Triazinesmentioning
confidence: 42%
“…The source of ALP includes synthesis in the intestinal epithelium, kidney, and liver and is often increased in response to a biliary obstruction. Velisek et al (2008) also reported decreased ALP in rainbow trout after acute exposure to metribuzin. Chronic exposure to terbutryn at 0.2 and 2 µg/L resulted in significant increase in plasma AST and LDH activity.…”
Section: Triazinesmentioning
confidence: 82%
See 1 more Smart Citation
“…Velisek et al (2008) described a significant (P < 0.01) decrease in total protein, triacylglycerids, AST, calcium and lactate in blood plasma of O. mykiss after a 96-h treatment with a metribuzin-based pesticide Sencor 70 WG at a concentration of 96-h LC50. In that study, glucose, ALT and LDH were not affected when compared to the control group.…”
Section: Discussionmentioning
confidence: 93%
“…Histopathological changes in gills of O. mykiss exposed to metribuzin (Sencor 70 WG) for 96 h were described as mild proliferation of goblet cells of the respiratory epithelium of the secondary gill lamellae. Other alterations were revealed in the caudal kidney and liver (Velisek et al 2008). …”
Section: Discussionmentioning
confidence: 96%